Significance of cerebellar tonsillar position on MR. - Barkovich, A J; Wippold, F J; Sherman, J L; Citrin, C M (American Journal of Neuroradiology, 1986)
It has been noted that a low degree of ectopia of the cerebellar tonsils on MR is of questionable significance. We measured the position of the cerebellar tonsils with respect to the inferior aspect of the foramen magnum in 200 normal patients and in 25 patients with a firm diagnosis of Chiari I malformation. In the normal group, the mean position of the tonsils was 1 mm above the foramen magnum with a range from 8 mm above the foramen magnum to 5 mm below. In the patients with Chiari I malformations, the mean position was 13 mm below the foramen magnum with a range from 3 mm below the foramen magnum to 29 mm below. Fourteen percent of normal patients had tonsils extending slightly below the foramen magnum. If 2 mm below the foramen magnum is taken as the lowest extent for tonsils in a normal patient, our sensitivity in predicting symptomatic patients is 100% and our specificity is 98.5% (three false positives). If 3 mm below the foramen magnum is taken as the lowest normal tonsillar position, our sensitivity is 96% and our specificity is 99.5%. MR demonstration of less than 2 mm of tonsillar ectopia is probably of no clinical significance in the absence of syringomyelia.